Intestinal glucose absorption in calves as affected by different carbohydrate sources. Issue 2 (28th February 2012) - Klinger, S.; Noci, B.; Müller, K.; Breves, G.
Summary: From numerous recent studies, it has been demonstrated that the development of the forestomach system in ruminants and thus microbial carbohydrate fermentation do not exclude the potential of the small intestines for enzymatic carbohydrate digestion and subsequent monosaccharide absorption. However, the role of regulatory nutritional factors is still under discussion. Therefore, we investigated the kinetic parameters of intestinal Na + ‐dependent glucose absorption and SGLT1 expression using isolated brush border membrane vesicles (BBMV) from the jejunum of 10‐week‐old calves kept on either hay, concentrate or corn silage‐based diets in addition to milk replacer. While the maximal transport capacity was significantly higher for concentrate and corn silage‐fed animals, SGLT1 protein expression was highest in BBMV isolated from hay‐fed animals. This observation differs from the prevalent conception that induction of Na + ‐dependent glucose uptake via SGLT1 is based on an increased number of transporters at the brush border membrane.